Let sleeping bears lie: an analysis of the factors behind Indonesia’s response to the Russo–Ukrainian war and its implications for the Indo-Pacific region - Sebastian, Leonard C. (2023)
This article discusses Indonesia’s pragmatic reaction to the war by adopting an equidistant foreign policy with both Russia and with Ukraine. It contends that three factors have shaped Indonesia’s response, namely Indonesian leaders’ perceptions and priorities regarding the country’s economic interests and its position as the President of the G-20; strategic ties with Russia; and bottom-up societal inclinations that favour Russia more than Ukraine. The article finds that the invasion of Ukraine affects Indonesia’s standing as the natural leader of ASEAN by undermining its cohesion and the organisation’s effectiveness and credibility for the leadership role it sought to play in the Indo-Pacific region. Furthermore, the war in Ukraine may have an impact on intensifying geopolitical rivalry in the region which may prompt the USA’s security partners in the region to fill the strategic void caused by Washington’s preoccupation with Eastern Europe contingencies.